Strategic leadership characteristics for Quality Malaysian National Primary Schools Education (QMNPSE) leaders - Mohd Ali, Hairuddin (2011)
Ministry of Education Malaysia (MOEM) formulated an Educational Master Plan (2006-2010) to ensure the achievement of National Mission. It is a continuation of the previous plan that emphasized on accessibility, equity, quality and as well as to enhance the educational management and leadership effectiveness and efficiency aspect. The purpose of this study is to examine the strategic leadership characteristics for quality Malaysian National Primary School Education (QMNPSE) leaders and how the findings of the study implicate the present practices of educational and leadership, that are pertinent to quality education for all in Malaysia. Approximately 600 senior management team comprised senior teachers from 150 schools were randomly selected to complete the 10-pages survey questionnaires (52 seven-point Likert scale items). The collection centre received approximately 420 completed survey questionnaires from the sampled schools. The employment of data screening process finally omitted 14 out of 420 cases prior to further data analysis. The study employed a full fledge Structural Equation Modeling (SEM) software AMOS 7.0 and SPSS 15.0 to confirm the dimensionality and the psychometric properties of the scales respectively. Although Davies and Davies (2004) suggested that strategic school leaders must posses all nine (9) strategic leadership characteristics, however the study confirmed that Malaysian Primary School Leaders only possess six (6) out of nine stipulated characteristics. One out of 2 missing characteristics was ‘wisdom’, which is of extremely important for an efficient and effective leadership in his/her capacity to realize the MOEM Master Plan particularly at grassroots level. The findings from the study provide useful information to senior management team members of the respective schools, District and States Education Department and IAB as well. IAB as an educational leadership training wing for MOEM perhaps need to restructure its training curriculum and the delivery of training as well. At least these two pertinent aspects, to certain extent will contribute to the achievement of the goals (mainly accessibility, equity, quality and as well as to enhance the educational management effectiveness and efficiency) stipulated in the MOEM Education Master Plan (2006-2010).